2009
DOI: 10.1073/pnas.0901754106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the core editing complex (L-complex) involved in uridine insertion/deletion RNA editing in trypanosomatid mitochondria

Abstract: Uridine insertion/deletion RNA editing is a unique form of posttranscriptional RNA processing that occurs in mitochondria of kinetoplastid protists. We have carried out 3D structural analyses of the core editing complex or ''L (ligase)-complex'' from Leishmania tarentolae mitochondria isolated by the tandem affinity purification procedure (TAP). The purified material, sedimented at 20 -25S, migrated in a blue native gel at 1 MDa and exhibited both precleaved and full-cycle gRNA-mediated U-insertion and U-delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 23 publications
(29 reference statements)
2
47
0
Order By: Relevance
“…Our CXMS data creates a detailed framework for the global architecture of editosome complexes, and can therefore provide context to reinterpret existing low-resolution electron microscopy data. For example, electron microscopy images of TAP-purified editosomes from T. brucei and Leishmania tarentolae revealed bipartite particles composed of two approximately equally sized, but structurally different globular domains that are connected via an interface (70,71). These studies also indicated that most editosome proteins are likely present as single copies in the complex, although the exact stoichiometry of editosomes remains unknown.…”
Section: Discussionmentioning
confidence: 81%
“…Our CXMS data creates a detailed framework for the global architecture of editosome complexes, and can therefore provide context to reinterpret existing low-resolution electron microscopy data. For example, electron microscopy images of TAP-purified editosomes from T. brucei and Leishmania tarentolae revealed bipartite particles composed of two approximately equally sized, but structurally different globular domains that are connected via an interface (70,71). These studies also indicated that most editosome proteins are likely present as single copies in the complex, although the exact stoichiometry of editosomes remains unknown.…”
Section: Discussionmentioning
confidence: 81%
“…Tb REH1 was detected by mass spectrometry analysis in an MP63-immunoprecipitated sample and also in a RECC preparation isolated by ion-exchange chromatography (32)(33)(34). However, REH1 was not detected in REN1-, REN2-, or REN3-TAP pull-downs from T. brucei (32,35), nor in REL1-TAP and MP44-TAP pull-downs from L. tarentolae (7,11). These results could be explained by our finding that REH1 is associated with the RECC by RNA linkers, as are several other editingassociated complexes (6,11), and that this linkage is easily disrupted during the isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining proteins contain a variety of motifs including zinc fingers, single-strand binding (SSB), and OB folds, and the roles of these proteins in the editing reaction are not known, although several are required for structural stability of the RECC. Low-resolution cryoEM 3D structures for RECC particles from Trypanosoma brucei and Leishmania tarentolae have been published (7,10), but these do not have sufficient resolution to shed light on the precise mechanisms involved in the editing reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be investigated how the architecture of the core of the editosome described in this work can be integrated with the recently reported three-dimensional structures of 20S editosomes (55,56). Golas et al (56), using complexes purified via tagged KREPA3, reported a bipartite appearance in the majority of their structures, which might reflect the division into FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%